Alergia às proteínas do leite de vaca e a atenção primária à saúde: uma revisão narrativa das diretrizes atuais - Carlos Tourinho Lapa Filho; Hannah Fernandes Lapa; Jackeline Motta Franco; Sarah Cristina Fontes Vieira; Dirceu Solé; Mário César Vieira; Ricardo Queiroz Gurgel (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVES: To perform a narrative review of the literature about current guidelines for food allergy and present the main recommendations for Cow's Milk Protein Allergy (CMPA) management in children at primary health care by algorithms. METHODS: We searched for relevant publications on the Cochrane Library, MEDLINE, PubMed, Guidelines International Network, National Guidelines Clearinghouse and National Institute for Health and Clinical Excellence (NICE) using the keywords on this topic. We made a comprehensive review of these publications as well as the recommendations of the Brazilian guide and consensus for food allergy. FINAL REMARKS: Adequate diagnosis and treatment for CMPA in children is essential, considering its nutritional, emotional and socioeconomic burden. Clinical practice guidelines provide recommendations based on scientific evidence improving quality of care; however, their implementation is challenging due to the lack of practical algorithms applicable and accessible for the management of CMPA in primary care. In addition, the lack of algorithms that favor accessibility to information from the extensive scientific content available is a reality that makes relevant a more practical proposal for a management of CMPA, applicable and accessible in order to consolidate a clinical practice based on scientific evidence.